Phase 2 study of hyper‐CMAD with liposomal vincristine for patients with newly diagnosed acute lymphoblastic leukemia. Issue 7 (24th April 2020) - Sasaki, Koji; Kantarjian, Hagop; Wierda, William; Ravandi‐Kashani, Farhad; Jorgensen, Jeffrey; Wang, Sa A.; Khoury, Joseph; Daver, Naval; Burger, Jan; Di Nardo, Courtney D.; Jain, Nitin; Short, Nicholas J.; et al.
Abstract: Liposomal vincristine is designed to reduce neurotoxicity and increase dose intensity delivery, and has been approved as salvage therapy in relapsed/refractory acute lymphoblastic leukemia (ALL). Our aim was to evaluate the response rate, toxicities, and outcome of adults with newly diagnosed ALL who received liposomal vincristine, rather than regular vincristine in combination with intensive chemotherapy (Hyper‐CMAD). In a single‐center, phase 2 study, patients ≥18 years with newly‐diagnosed B‐cell ALL were eligible to receive hyper‐CMAD alternating with high‐dose methotrexate and cytarabine. Rituximab was administered in CD20 positive ALL. Tyrosine kinase inhibitors (imatinib or dasatinib) were added in Philadelphia chromosome‐positive (Ph‐positive) ALL. Thirty‐one patients were enrolled, median follow‐up of 59 months (0.3‐70). Thirteen patients (42%) had CD20 positive ALL, and 21 (68%) had Ph‐positive ALL. Thirty (97%) achieved complete remission (CR). All 26 patients with abnormal karyotype achieved complete cytogenetic response (CCyR), and 27/30 (90%) achieved negative minimal residual disease status by multicolor flow cytometry. Of 20 evaluable Ph‐positive ALL patients, major molecular response (MMR) was achieved in 19 patients (95%); complete molecular response (CMR) in 14 (70%). Grade 3/4 peripheral neuropathy was observed in five (16%) with all grade peripheral neuropathy in 21 (68%). With a median follow‐up of 59 months, 21 (68%) patients are alive. The 5‐year CR duration and survival rates were 73% and 61%, respectively. Ten (32%) patients died: one, sepsis on C1D10; four, unknown; one, post‐transplant complications; four, relapse. Hyper‐CMAD with liposomal vincristine is safe and demonstrated high response and survival rates in newly diagnosed ALL.